Does estimation of prostate volume by abdominal ultrasonography vary with bladder volume: A prospective study with transrectal ultrasonography as a reference - Shivadeo S Bapat; Satyajeet S Purnapatre; Ketan V Pai; Pushkaraj Yadav; Abhijit Padhye; Y G Bodhe (Indian Journal of Urology, 2006)
Objectives: Ultrasonography (USG) is the commonest modality for ascertaining prostate volume. Urologists commonly encounter a discrepancy between prostate volume on USG and actual volume of prostate, whereas transrectal ultrasonography (TRUS) gives near correct prostate volume. We undertook a prospective study to compare the relationship between changing bladder volumes to the volume of prostate. Materials and Methods: After approval of the Institutional Ethics Committee and informed consent, 25 patients (age group: 52-78 years) with lower urinary tract symptoms were assessed for prostate volume by USG at different bladder volumes and final comparison was done with TRUS in one setting. Each USG and TRUS was done by one urology resident under the guidance of one qualified radiologist with experience of over 15 years in this field. Equipment used was SIEMENS SONNOLINE ADARA with 3.5 MHz probe for USG and 7.5 MHz Endo p-2 (biplaner) probe for TRUS. First, patients were asked to empty their bladder and post void residual urine was measured along with prostate volume. Patients were given oral fluids and USG was repeated serially at three intervals with bladder volume of 100-200 ml, 200-300 ml and > 300 ml. Finally uroflowmetry was carried out followed by TRUS. Results were recorded in a tabulated form on ′Excel spread sheet′. Results: 1. Measurement of prostate volume increases with increase in bladder volume. 2. Calculated prostate volume at minimal bladder capacity (100-200 ml) was found to be the closest to the volume calculated by TRUS. Conclusion: Minimal bladder volume (100-200 ml) is essential for near correct estimation of prostate volume by USG. With increasing bladder volume, the volume of prostate increases disproportionate to its actual volume.